2013
DOI: 10.1074/mcp.m112.026534
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Proteome Responses of Pathogenic and Nonpathogenic Aspergilli to Human Serum Measured by Activity-Based Protein Profiling (ABPP)

Abstract: Aspergillus fumigatus is the primary pathogen causing the devastating pulmonary disease Invasive Aspergillosis in immunocompromised individuals. There is high genomic synteny between A. fumigatus and closely related rarely pathogenic Neosartorya fischeri and Aspergillus clavatus genomes. We applied activity-based protein profiling to compare unique or overexpressed activitybased probe-reactive proteins of all three fungi over time in minimal media growth and in response to human serum. We found 360 probe-react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Using a FP-probe multiplexed with a probe that targets enzymes with reactive cysteines in the fungus Aspergillus fumigatus, a human pathogen that is difficult to detect and for which no known virulence proteins are known, our group found that in the presence of host serum the organism alters physiological functions throughout numerous metabolic processes [12]. A follow-up study comparing A. fumigatus to two highly related but non-pathogenic fungi further confirmed the metabolic attenuation of A. fumigatus in the presence of the host, and the disparate metabolism in the presence of host was not identified in the other fungi [13]. Thereby, ABPP facilitated an improved understanding of the fungi"s pathogenesis mechanism, and an array of proteins was identified as potential disease candidate biomarkers.…”
Section: Activity-based Protein Profiling With Antibiotic Derived Probesmentioning
confidence: 90%
See 1 more Smart Citation
“…Using a FP-probe multiplexed with a probe that targets enzymes with reactive cysteines in the fungus Aspergillus fumigatus, a human pathogen that is difficult to detect and for which no known virulence proteins are known, our group found that in the presence of host serum the organism alters physiological functions throughout numerous metabolic processes [12]. A follow-up study comparing A. fumigatus to two highly related but non-pathogenic fungi further confirmed the metabolic attenuation of A. fumigatus in the presence of the host, and the disparate metabolism in the presence of host was not identified in the other fungi [13]. Thereby, ABPP facilitated an improved understanding of the fungi"s pathogenesis mechanism, and an array of proteins was identified as potential disease candidate biomarkers.…”
Section: Activity-based Protein Profiling With Antibiotic Derived Probesmentioning
confidence: 90%
“…Studies to identify virulence mechanisms in A. fumigatus [12,13]. Characterized Glpg in E. coli [14].…”
Section: Representative Probes and Their Applicationmentioning
confidence: 99%
“…While the mechanisms exploited by fungi to evade the immune system have been studied in detail, the subsequent fungal intracellular response after binding and sensing of host serum proteins is less clear. Proteomic analysis of Aspergillus species after incubation with human serum revealed a divergent response in pathogenic A. fumigatus compared with less pathogenic species (Wiedner et al, 2013). Thus, a direct connection between sensing of host factors and adaptation to a host environment with virulence and resistance seems to exist.…”
Section: Serum Factorsmentioning
confidence: 97%
“…The authors would like to apologize to all the scientists with relevant contributions in the field, whose work could not be cited as a result of space limitations. Moreover, the authors would like to thank the organizers of the fungal cell wall meeting, held in Paris 26-28 October (Wiedner et al, 2013) Fungal sensing 1195 2015, for enabling fruitful scientific exchange between different fields of fungal research and initiating the writing of this review. We declare that there is no conflict of interest.…”
Section: Acknowledgementmentioning
confidence: 99%
“…The same group used a non-directed phenyl sulfonate ester probe to target a broad range of enzyme families and showed that HCV infection led to dysregulation of several protein activities that may be relevant to HCV replication (15). Wright and colleagues recently used a cysteine-reactive sulfonate ester probe and the serine hydrolase probe to identify several dysregulated enzyme activities in Aspergillus fumigatus, the primary pathogen causing the devastating pulmonary disease Invasive Aspergillosis (16). The same group also developed activity-based probes for cellulose degrading enzymes in Clostridium thermocellum which may have applications in biofuel development (17).…”
Section: Broad Profiling Of Enzyme Activitiesmentioning
confidence: 99%